Effect of socioeconomic status on stage at diagnosis of lung cancer in a hospital‐based multicenter retrospective clinical epidemiological study in China, 2005–2014. (21st September 2017) - Li, Yuanqiu; Shi, Jufang; Yu, Shicheng; Wang, Le; Liu, Jianjun; Ren, Jiansong; Gao, Shugeng; Hui, Zhouguang; Li, Junling; Wu, Ning; Yang, Boyan; Liu, Shangmei; et al.
Abstract : To date, the role of socioeconomic status (SES), either at the individual or community level, in shaping lung cancer risk has been only measured in non‐Chinese populations, and the association is inconsistent. This is the first study to consider, simultaneously, measures of SES at the individual and area levels in China, in which the most socioeconomically deprived areas is associated with a higher risk of advanced‐stage lung cancer compared with the least deprived areas. Abstract: There is inconsistent evidence of associations between socioeconomic status (SES) and lung cancer stage in non‐Chinese populations up to now. We set out to determine how SES affects stage at diagnosis at both individual and area levels, from a hospital‐based multicenter 10‐year (2005–2014) retrospective clinical epidemiological study of 7184 primary lung cancer patients in mainland China. Individual‐level SES data were measured based on two indicators from case report forms of the study: an individual's education and occupation. Seven census indicator variables were used as surrogates for the area‐level SES with principal component analysis (PCA). Multivariate analysis was undertaken using binary logistic regressions and multinomial logit model to describe the association and explore the effect across tertiles on stage after adjusting for demographic variables. There was a significant stepwise gradient of effect across different stages in the highest tertile of area‐level SES, comparing with the lowest tertile of area‐level SES (ORs, 0.77, 0.67, and 0.29 for stage II, III, and IV). Patients with higher education were less likely to have stage IV lung cancer, comparing with the illiterate group (ORs, 0.52, 0.63, 0.71, 0.64 for primary school, middle school, high school, college degree or above subgroup, respectively). Findings suggest that the most socioeconomically deprived areas may be associated with a higher risk of advanced‐stage lung cancer, and increasing educational level may be correlated with a lower risk to be diagnosed at advanced stage in both men and women.